Human Health Risk Assessment of Heavy-metal Exposure in Soil and Water from Oil-producing Communities of Delta State, Nigeria: An Audited Reassessment - Sanda Yusuf Sadau; N. Rabiu; N. N. Garba; Suleiman Bello; Ishaya Iliyasu; Tina Abimbola Adeniji (Asian Journal of Physical and Chemical Sciences, 2026)
Heavy-metal contamination in oil-producing environments may create human-health concerns through ingestion, inhalation and dermal exposure. This study reassessed non-carcinogenic and carcinogenic risks associated with Ni, Cr, Cu, Co, Pb, Cd, Fe, Mn, As and Zn in soil and water from the Apkai and Umusedege communities, Delta State, Nigeria, while auditing inconsistencies between thesis narrative summaries and numerical appendices. Concentrations were determined using atomic absorption spectrometry, with X-ray fluorescence used to validate soil results. Risk was evaluated using average daily intake, hazard quotient, hazard index and excess lifetime cancer risk for children and adults. The audit confirmed soil hazard indices of 2.51 for children and 1.29 for adults. Recalculation of water components yielded hazard indices of 0.02 for children and 12.31 for adults, producing corrected overall values of 2.53 and 13.60, respectively. For carcinogenic risk, an exponent error in the adult soil total was corrected to 1.85×10⁻⁶. Corrected total excess lifetime cancer risks were 7.18×10⁻⁶ for children and 2.40×10⁻⁶ for adults, both below the adopted 1×10⁻⁴ upper screening level. Soil ingestion dominated non-carcinogenic soil risk, whereas ingestion was the principal carcinogenic pathway. The unusually large adult water dermal hazard quotient of 12.04 requires independent verification. Overall, the audited results identify non-carcinogenic risk as the main modelled health concern.